If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 14 + 12 = -5x + 2x Combine like terms: 14 + 12 = 26 26 = -5x + 2x Combine like terms: -5x + 2x = -3x 26 = -3x Solving 26 = -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. 26 + 3x = -3x + 3x Combine like terms: -3x + 3x = 0 26 + 3x = 0 Add '-26' to each side of the equation. 26 + -26 + 3x = 0 + -26 Combine like terms: 26 + -26 = 0 0 + 3x = 0 + -26 3x = 0 + -26 Combine like terms: 0 + -26 = -26 3x = -26 Divide each side by '3'. x = -8.666666667 Simplifying x = -8.666666667
| 12=-3(-2)-4y | | 5-2[x-4]=-11 | | -8v-22=6(v+1) | | 10-(-1x)=17x+2 | | x=-1.75+(.5-.125x) | | -2x+-2=2x-2 | | p-8=-9+p | | 20v^2+11v-3=0 | | 4x-4=5x-5+3x+6 | | 5a+30=6a+16 | | 2x+12+5x-9+6x-2=180 | | 13-(2c+2)=2c(c+2)+3c | | 216=8(5a+71) | | 9x-10y=-1 | | 5(x+2)=8x+1 | | 4x^4+10x^3y-6x^2y^2=0 | | log(2)(7x+6)=3 | | (2x-5y)-(x+y)= | | 6x+4=6x-3 | | 1.75x^3+2.5x^2=6.25x | | -17+x=63 | | (3x+5)-7=42 | | 4(1+4n)=-124 | | 3x+6=4x-17 | | 27x+9y=54 | | 4x-6-9x+1=0 | | 8(x-6)=-88 | | -3x+36=-18 | | 6b^2+13b-63= | | 3/4*2/7= | | 8*9n=96 | | 19-(2x+3)=2(x+3) |